Prove the equivalence of the following in three different ways (truth table, simplification,
each is a logical consequence of the other): p → (q ∨ r) ≡ (p ∧ ~q) → r.
We prove the equivalence using the truth table.
We see that the formulas p → (q ∨ r) and (p ∧ ~q) → r take the same truth value therefore the formulas are equivalent.Proven.
Prove by simplifying:
"p \\to \\left( {q \\vee r} \\right) \\equiv \\sim p \\vee q \\vee r"
"\\left( {p \\wedge \\sim q} \\right) \\to r \\equiv \\sim \\left( {p \\wedge \\sim q} \\right) \\vee r \\equiv \\sim p \\vee q \\vee r"
It's obvious that "\\sim p \\vee q \\vee r \\equiv \\sim p \\vee q \\vee r \\Rightarrow p \\to \\left( {q \\vee r} \\right) \\equiv \\left( {p \\wedge \\sim q} \\right) \\to r" . Proven.
Show that (p ∧ ~q) → r is a logical consequence of p → (q ∨ r).
Let p → (q ∨ r) ≡1. Let's say that (p ∧ ~q) → r ≡0. Then (p ∧ ~q) ≡1 and r ≡0, but then p ≡1 and q≡0. Then p → (q ∨ r) ≡1→(0 ∨ 0)≡0 - we have a contradiction. Therefore, if p → (q ∨ r) ≡1 then (p ∧ ~q) → r ≡1, so "\\left. {p \\to \\left( {q \\vee r} \\right)} \\right| = \\left( {p \\wedge \\sim q} \\right) \\to r" .
Show that p → (q ∨ r) is a logical consequence of (p ∧ ~q) → r.
Let (p ∧ ~q) → r≡1. Let's say that p → (q ∨ r) ≡0. Then p ≡1 and (q ∨ r) ≡0. Then q ≡r≡0. But then (p ∧ ~q) → r≡(1 ∧1)→0≡0 - we have a contradiction. Therefore, if (p ∧ ~q) → r≡1 then p → (q ∨ r) ≡1, so "\\left. {\\left( {p \\wedge \\sim q} \\right) \\to r} \\right| = p \\to \\left( {q \\vee r} \\right)" .
We have "\\left. {p \\to \\left( {q \\vee r} \\right)} \\right| = \\left( {p \\wedge \\sim q} \\right) \\to r" and "\\left. {\\left( {p \\wedge \\sim q} \\right) \\to r} \\right| = p \\to \\left( {q \\vee r} \\right)" , therefore p → (q ∨ r) ≡ (p ∧ ~q) → r. Proven.
Comments
Leave a comment